Are we Athens or Florence? COVID-19 in historical context. Issue 1 (1st February 2021) - Doolittle, Benjamin R
Abstract : We have been here before. In 430 BCE, a plague struck Athens, killing as much as 25% of the population. In 1347 CE, the bubonic plague afflicted western Europe for 4 years, killing as much as 50% of the population. The plague of Athens led to a collapse of their religion, cultural norms and democracy. In contrast, the bubonic plague led eventually to the Renaissance, a growth of art, science and humanism. As we contend with the COVID-19 global pandemic, will we become Athens or Florence?